GRAPH IMAGE LANGUAGES IN SEMANTIC DESCRIPTION OF SPATIAL CORONARY ARTERIES STRUCTURE - Ogiela, Marek; Trzupek, Mirosław (Computer Science, 2013)
In this paper has been proposed developing the new syntactic – semantic meaning descriptionof spatial coronary arteries structure. Thanks such description will be possible to makeessentially steered semantic interpretation of section coronary arteries morphology, what willallow us fast identiﬁcation and automatisation of lumen stricture detection. In this aim hasbeen used graph image languages based on the expansive graph grammars of edNLC type,enabling creation the universal and informative meaning description of spatial coronaryarteries structure. Application of such semantic description in the integrated modules ofintelligent systems medical diagonosis, supporting the early detection stricture which defectthe ﬂow of oxidizing blood to given area of cardiac muscle.